Management of advanced ovarian cancer in Leicester: The benefits of a paradigm shift in surgical approach. Issue 12 (23rd September 2022) - Barakat, Anas; Ismail, Aemn; Chattopadhyay, Supratik
Abstract: Aim: Surgery for advanced ovarian cancer (AOC) has evolved over the past decade to ingeminate the need to offer maximum effort surgery (MES). The aim of this study is to analyze the implementation of a paradigm shift in the surgical management of women with AOC at the University Hospitals of Leicester NHS Trust (UHL) in 2015, until 2020, compared to 2011–2014. Methods: Retrospective cohort study of women with AOC who underwent cytoreductive surgery (CRS) in the UHL. The two groups were: 153 women from January 2011 to December 2014 (group 1), 136 women from January 2015 to January 2020 (group 2). Results: In group 1, the 1, 3, and 5 years overall survival rates (OS) were, 90.4%, 33.7%, and 19.3%, compared to 90.2%, 55.4%, and 29.7%, respectively, in group 2 ( p  = 0.012). Significantly more women had CRS in group 2: 45—Primary debulking surgery (PDS) and 57—interval debulking surgery (IDS) versus 17—PDS & 67—IDS in group 1 ( p  < 0.001). Surgical complexity score (modified Aletti score) was higher in group 2 compared to group 1 ( p  = <0.001). No significant difference was noted in the postoperative complications, in group 2, in women who underwent PDS versus IDS, yet PDS was associated with higher OS. Conclusions: MES/CRS in women with AOC significantly improves OS. Our data highlights the importance of a dedicated team to implement this change in cancer centers. Where possible, suitable women with AOC likely to have complete cytoreduction based on preoperative assessment, should be offered PDS.